2019
DOI: 10.1109/tnsre.2019.2893949
|View full text |Cite
|
Sign up to set email alerts
|

Between-Frequency Topographical and Dynamic High-Order Functional Connectivity for Driving Drowsiness Assessment

Abstract: Previous studies exploring driving drowsiness utilized spectral power and functional connectivity without considering between-frequency and more complex synchronizations. To complement such lacks, we explored interregional synchronizations based on the topographical and dynamic properties between frequency bands using high-order functional connectivity (HOFC) and envelope correlation. We proposed the dynamic interactions of HOFC, associated-HOFC, and a global metric measuring the aggregated effect of the funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 32 publications
1
18
0
1
Order By: Relevance
“…Other features, such as functional connectivity [40,41] and entropy [20,42], could be used in the proposed framework as these features have been proven to be of discriminative power in the differentiation between alertness and fatigue. Most recently, high-order functional connectivity in both static and dynamic representations was found to have complementary information to low-order functional connectivity in fatigue detection [43]. These diverse kinds of features can be fused to improve fatigue classification [44].…”
Section: Ieee Transactions On Cognitive and Developmental Systemsmentioning
confidence: 99%
“…Other features, such as functional connectivity [40,41] and entropy [20,42], could be used in the proposed framework as these features have been proven to be of discriminative power in the differentiation between alertness and fatigue. Most recently, high-order functional connectivity in both static and dynamic representations was found to have complementary information to low-order functional connectivity in fatigue detection [43]. These diverse kinds of features can be fused to improve fatigue classification [44].…”
Section: Ieee Transactions On Cognitive and Developmental Systemsmentioning
confidence: 99%
“…The studies found that when mental fatigue level increases due to vigilance tasks, the functional coupling decreased, specifically over the parietal-to-frontal areas in individual theta, alpha and beta frequency bands. However, for the simulated driving task, studies have reported an increase in the connectivity network in the frontal-central, and central-parietal/occipital areas at the end of driving sessions [39], [40], [41]. Besides, a recent study has reported both; decrease and increase in the connectivity networks in driving fatigue [42].…”
Section: Introductionmentioning
confidence: 97%
“…[36,37] 、相位同步(phase synchronization) [38] 、同步 似然(synchronization likelihood) [39,40] 、Granger因 果 [41,42] 、自适应直接传递函数(adaptive directed transfer function, ADTF) [43] 、跨频耦合(cross-frequency coupling) [44] 以及一些其他方法 [45~47] . 网络分析方法, 主要 有基于图论的分析方法 [48,49] 、时变脑网络分析 [50,51] 、 网络动态分析 [52~54] 、网络重组 [55,56] 、多层网络 [57,58] 、 高阶网络 [59] 等. 最近出现的网络分析处理算法则有Lp 范数Granger因果有向网络分析方法和Lp(p≤1)范数偏 有向相干(partial directed coherence)网络分析方法, 这 些方法能在噪声情况下比较准确地估计出网络连接模 式 [60,61] .…”
Section: 在频域上 除了传统的傅里叶变换、小波分析等unclassified